Effect of Vermicompost on Soil and Runoff Properties in Northern Iran. Issue 3 (1st October 2020) - Pasha, Maryam Rezaei; Shahedi, Kaka; Vahabzadeh, Qorban; Kavian, Ataollah; Sepanlou, Mehdi Ghajar; Jouquet, Pascal
Abstract: This study aimed at measuring the effect of vermicompost on soil physical and chemical properties and runoff quality and quantity in agro-ecosystems in Northern Iran. Thus, runoff measurement plots of 1 × 5 m were set up in sloping lands under natural rainfall during 5 months. Runoff quality and quantity, soil properties, and plant growth were measured. This study shows that the amount of runoff water and its quality (sediment yields, nitrate content, pH, and conductivity) were not influenced by the fertilization treatments (vermicompost alone, chemical fertilization alone, or their mixture), except for the first month of the experiment where a lower runoff amount was measured when vermicompost was applied alone. Although no difference in plant growth was found, our results showed a significant improvement of soil properties when vermicompost was used as a fertilizer. Consequently, this study shows that vermicompost can be considered as an alternative application for reducing the use of chemical fertilizers and improving soil properties but its impact on plant growth and runoff is limited to the short term.